Opportunities for Treg cell therapy for the treatment of human disease - Bluestone, Jeffrey A.; McKenzie, Brent S.; Beilke, Joshua; Ramsdell, Fred (Frontiers in Immunology, 2023)
Regulatory T (Treg) cells are essential for maintaining peripheral tolerance, preventing autoimmunity, and limiting chronic inflammatory diseases. This small CD4+ T cell population can develop in the thymus and in the peripheral tissues of the immune system through the expression of an epigenetically-stabilized transcription factor, FOXP3. Treg cells mediate their tolerogenic effects using multiple modes of action including: the production of inhibitory cytokines; cytokine starvation of T effector (e. g. IL-2); Teff suppression by metabolic disruption; and modulation of antigen presenting cell maturation or function. Together these activities result in broad control of various immune cell subsets, leading to the suppression of cell activation/expansion and effector functions. Moreover, these cells can facilitate tissue repair to complement their suppressive effects. In recent years, there has been an effort to harness Treg cells as a new therapeutic approach to treat autoimmune and other immunological diseases and, importantly, to re-establish tolerance. Recent synthetic biology advances have enabled the cells to be genetically engineered to achieve tolerance and antigen-specific immune suppression by increasing specific activity, stability, and efficacy. These cells are now being tested in clinical trials In this review, we highlight both the advances and challenges in this arena, focused on efforts develop this new pillar of medicine to treat and cure a variety of diseases.